Germany : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This report reviews the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism on Germany. In preparing the detailed assessment, assessors reviewed relevant AML and counterterrorist financing (CFT) laws and regulations; the supervisory and regulatory systems in place for banks, foreign exchange, securities, insurance, and money remittance; and criminal law enforcement systems. Germany is reviewing new legislation to re-address the issue of the criminalization of terrorist financing.